The Relationship between learning styles and personality traits of students from Boğaziçi University Faculty of Education - Yanardöner, Erdal. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
The purpose of this study was to investigate the relationship between learning styles and personality traits of students from Boğaziçi University Faculty of education. In addition to that purpose, description of learning styles, personality traits, and their relationship between gender, department and grade point average (GPA) were searched. Three instruments were used for data collection in the study. For collecting demographic information regarding to sample, demographic data form designed by researcher was used. In order to measure learning styles of students, the Kolb's Learning Style Inventory (1985) was used. Finally, to measure personality traits of students, the Big Five Inventory (1993) (John, Donahue & Kentle) was administered. The data were collected from 236 students during 2009-2010 summer term, and data of 224 students were considered valid. The findings of the study indicated that the majority of students had assimilator learning style, and there was not a significant relationship between students' learning styles and their genders, departments, and GPAs. Findings also showed that the majority of students' personality trait was agreeableness and there was not a significant relationship between students’ personality traits and their gender, departments, and GPAs. Finally, according to the findings of the present study, no significant relationship was found between learning styles and personality traits of students.
Keywords: Learning strategies.